Beneficial effects of apple peel polyphenols on vascular endothelial dysfunction and liver injury in high choline-fed mice. Issue 3 (27th February 2017) - Jia, Mengfan; Ren, Daoyuan; Nie, Yan; Yang, Xingbin
Abstract : APP could ameliorate HC diet-induced vascular dysfunction and hepatic injury. Abstract : This study was designed to investigate the preventive effects of Red Fuji apple peel polyphenolic extract (APP) on vascular endothelial dysfunction and liver injury in mice fed a high choline diet. The mice were fed 3% dietary choline in drinking water for 8 weeks and displayed vascular dysfunction and liver damage ( p < 0.01). The administration of APP at 600 and 900 mg per kg bw significantly elevated serum NO, HDL and 6-Keto-PGF1a levels and lowered serum TC, TG, LDL, ET-1 and TXB2 levels in the HC-fed mice. Besides, APP also caused the reduction of AST, ALT activities and MDA, CRP, TNF-α levels, and increased the hepatic GSH-Px and SOD activities of the HC-fed mice. Furthermore, the histopathology of the liver by conventional H&E and oil red O staining confirmed the liver steatosis induced by a choline diet and the hepatoprotective effect of APP. The experiment results indicated that the polyphenolic extract from apple peel might be regarded as a preventive and therapeutic product for the amelioration of HC diet-induced vascular dysfunction and hepatic injury.